Nitrogen Uptake, Not Transfer of Carbon and Nitrogen by CMN, Explains the Effect of AMF on the Competitive Interactions Between Flaveria bidentis and Native Species - Chen, Xue; Li, Qiao; Wang, Liting; Meng, Yanliang; Jiao, Shaona; Yin, Jilin; Xu, Haiyun; Zhang, Fengjuan (Frontiers in Ecology and Evolution, 2021)
Rhizophagus intraradices is one of the common arbuscular mycorrhizal fungi (AMF) in the roots of Flaveria bidentis, which facilitates its invasion. However, we did not know whether nutrient transfer through the common mycorrhizal networks (CMN) between the exotic and the native species enhanced its competitive growth. To elucidate the related mechanism isotopic labeling technology were used to test the transfer of carbon and nitrogen by CMN. PVC box, which contained compartments A, B and C, was used to in the experiment. Compartment B was set up to minimize the risk of free transfer of C and N between compartments A and C. A nylon mesh of pore size 30 μm was added in compartments A and C to prevent penetration by roots while allowing hyphal penetration. The results showed that the corrected index of relative competition intensity (CRCI) of F. bidentis in the presence of AMF < 0, suggesting competition facilitated F. bidentis growth whether with S. viridis or with E. prostrata. The reason was that R. intraradices inoculation significantly increased the carbon and nitrogen contents of F. bidentis in the mixtures. However, the effects of R. intraradices on two native species were different: negative effect on the growth of S. viridis, while positive effect on the growth of E. prostrata. The change of nitrogen content in S. viridis or E. prostrata was consistant with the variation of the biomass, suggesting nitrogen uptake explains the effects of Rhizophagus intraradices on the competitive interactions between Flaveria bidentis and two native species. Moreover, the transfer of carbon and nitrogen via AMF hyphal links did occur between F. bidentis and native species. F. bidentis showed a lower ability to gain carbon and nitrogen through CMN than S. viridis, while it showed a higher ability to gain carbon and nitrogen through CMN than E. prostrata. The results showed that the transfer of carbon and nitrogen by CMN was not positively related with the competitive growth.